Adenium obesum as a new potted flower: growth management - Colombo,Ronan Carlos (2018)
ABSTRACT Adenium obesum, also known as desert rose, has recently become popular in Brazil, due to its exuberance and sculptural shape. However, the production of the species in commercial scale has been facing challenges regarding propagation of hybrids by in vitro cultivation techniques, potting medium composition, irrigation and fertilization management, disease and pest control. Unlike other species sold as potted plants, there are no commercial production protocols established for Adenium, mainly due to the scarcity of technical information about this species. Thus, this technical article aimed to provide information related to the Adenium growth, in view of its commercial scale production. In addition, aspects related to floral morphology, pollination and seed production of the species, as well as, vegetative propagation strategies were discussed.